Profile of Students' Cognitive Learning Outcome Completeness in Biotechnology Learning Through Kahoot-Assisted Game Tournament Teams - Radif Nur R.A; Ipah Budi Minarti; Eny Hartadiyati W.H; Risno Setiyono (JURNAL PAJAR (Pendidikan dan Pengajaran), 2023)
Biotechnology material is closely related to the use of biological sciences to support everyday life so the learning process should be implemented in a fun teaching and learning method to enhance students' understanding. The Teams Game Tournament learning model is an appropriate model to create a fun teaching and learning atmosphere for students because based on its implementation the learning is set in the form of a tournament among the students. In terms of its implementation, the Teams Game Tournament that is assisted by Kahoot will further enhance the learning attractiveness. The purpose of the study was to find out the profile of students' cognitive learning outcome completeness in biotechnology learning through the Kahoot-assisted Teams Game Tournament. The research type was a pre-experimental design with a one-shot case study research design. The research subjects involved 36 students of class XII IPA 3 of SMA Islam Sultan Agung 1 Semarang. The research results indicate that students complete biotechnology learning using the Kahoot-assisted Teams Game Tournament model. It is seen from the average score of 84.4, which is above the KKM score of 77. In addition, it is corroborated by data analysis, which indicates that the value of Sig. (2-tailed) is 0.002 <0.05 = α, and tcount > ttable.